Reducing Hospital-Acquired Infections: Collaborative Efforts from Dentists, Operation Technicians, Pharmacists, Radiologists, Nurses, Optometric technicians and Physiotherapists - Mejhez Saud Alotaibi7, Bander Ali Alrashdi8, Majedah Fehan Saud Alshammari9, Saud Mohammed Altamimi10, Abdulaziz Eid Alhamzani11, Hamza Zaki Alhussaini12, Salman Saad Mohammad Shaber13 Omar Mohamed Amer Asiri 14, Mashael Mousaa Faraj Marzoq1, Adel Mohammed Almubadel2, Omama Shafeeq. Abualsaud3, Zahra Hassan Ramadan4, Sultan Ahmed Alloqmani5, Faisal Abdulrahman Alsanee6 (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Hospital-acquired infections (HAIs) pose significant challenges to healthcare systems worldwide, leading to increased morbidity, mortality, and financial burdens. This paper explores the roles of various healthcare professionals in reducing HAIs through collaborative infection control efforts. Dentists, operating room technicians, pharmacists, radiologists, nurses, and physiotherapists each play crucial roles in implementing infection prevention practices and promoting antimicrobial stewardship. Through adherence to guidelines, such as proper hand hygiene, sterilization techniques, and judicious antibiotic use, these professionals contribute to minimizing the transmission of pathogens in healthcare settings. Interprofessional collaboration, evidenced by infection control bundles and antibiotic stewardship programs, further enhances patient safety and healthcare outcomes. This paper highlights the necessity of recognizing and integrating the diverse expertise of healthcare professionals in combating HAIs.